Madu Sebagai Obat Dalam Perspektif Al-Qur’an: An-Nahl 68-69 - Kaysa Billah; Nilla Sari; Ali Akbar (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Honey is one of the natural substances that has been used as medicine for thousands of years. In the Qur'an, specifically in Surah An-Nahl verses 68-69, Allah explicitly mentions honey as containing shifa (healing) for humans. This article examines the concept of honey as medicine from a Qur'anic perspective by analyzing the interpretation of related verses, the scientific content of honey, and its relevance to modern health research. The method used is a literature review (library research) with a thematic (maudhu'i) interpretation approach. The research findings indicate that the Qur'an preceded modern scientific discoveries about the therapeutic properties of honey, and there is a strong correlation between the Qur'anic statements and contemporary scientific evidence regarding the benefits of honey as a healing agent.